Therapy related‐chronic myelomonocytic leukemia (CMML): Molecular, cytogenetic, and clinical distinctions from de novo CMML. Issue 1 (3rd November 2017) - Patnaik, Mrinal M.; Vallapureddy, Rangit; Yalniz, Fevzi F.; Hanson, Curtis A.; Ketterling, Rhett P.; Lasho, Terra L.; Finke, Christy; Al‐Kali, Aref; Gangat, Naseema; Tefferi, Ayalew
Abstract: Therapy related myeloid neoplasms (t‐MN) including therapy related myelodysplastic syndromes (t‐MDS) and acute myeloid leukemia (t‐AML) are associated with aggressive disease biologies and poor outcomes. In this large ( n = 497) and informative (inclusive of molecular and cytogenetic information) chronic myelomonocytic leukemia (CMML) patient cohort, we demonstrate key biological insights and an independent prognostic impact for t‐CMML. T‐CMML was diagnosed in 9% of patients and occurred approximately 7 years after exposure to prior chemotherapy and/or radiation therapy. In comparison to de novo CMML, t‐CMML patients had higher LDH levels, higher frequency of karyotypic abnormalities and had higher risk cytogenetic stratification. There were no differences in the distribution of gene mutations and unlike t‐MDS/AML, balanced chromosomal translocations, abnormalities of chromosome 11q23 (1%) and Tp53 mutations (<2%) were uncommon. Molecularly integrated CMML prognostic models were not effective in risk stratifying t‐CMML patients and responses to hypomethylating agents were dismal with no complete responses. Median overall (OS) and leukemia free survival (LFS) was shorter for t‐CMML in comparison to d‐CMML (Median OS 10.9 vs 26 months and median LFS 50 vs 127 months) and t‐CMML independently and adversely impacted OS ( P = .0001 HR 2.1 95% CI 1.4‐3.0). This prognostic impact was retained in the context of the Mayo Molecular Model ( P = .001, HR 2.4, 95% CI 1.5‐3.7) and the GFM prognostic model ( P < .0001, HR 2.15, 95% CI 1.5‐3.7). In summary, we highlight the unique genetics and independent prognostic impact of t‐CMML, warranting its inclusion as a separate entity in the classification schema for both CMML and t‐MN.